Semantic Change Type in Old Javanese Word and Sanskrit Loan Word to Modern Javanese - Yuniarto, Hendy; Marsono, Marsono (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2013)
This research aims to describe type classifier of semantic change and to explain the factors causing semantic change. This research was conducted with a qualitative-descriptive approach. The research method is conducted by comparing the meaning of words from the Old Javanese and Sanskrit loan wordto Modern Javanese. The collection data is done by looking for words that the meaning suspected change in Old Javanese dictionary. Words meaning determined precisely by tracing to the Old Javanese text. Furthermore, words meaning are compared to present time meaning through Modern Javanese dictionary. In addition, searching Modern Javanese meaning are also using Javanese news on the internet pages. The analysis of this research is to classify Old Javanese words and Sanskrit loan words meaning that undergo change to Modern Javanese. Its also explained why the change in the word meaning can occur. The result shows that, semantic change of Old Javanese words and Sanskrit loan words to Modern Javanese can be classified into seven types, involving widening, narrowing, shifting, metaphor, metonymy, pejoration, and euphemism. In addition, the result shows that semantic change can occur because of some factors. Psychological factor concerning emotive and taboo, and polysemy. religion spreading, the growth of science and technology, the socio-political development, and the needs of a new name.